Addressing barriers to vaccine acceptance: an overview. Issue 1 (2nd January 2018) - MacDonald, Noni E.; Butler, Robb; Dubé, Eve
ABSTRACT: Addressing the drivers of vaccine hesitancy and the barriers to vaccine acceptance is a complex but important task. While the percentage of hesitant does vary from country to country and in time few, if any, countries are ever free from this problem. Overcoming hesitancy requires detection, diagnosis and tailored intervention as there is no simple strategy that can address all of the barriers to vaccine acceptance. Immunization program managers and health care workers need to become adept at recognizing and tackling hesitancy in all of its incarnations if high levels of vaccine acceptance are to be achieved but must also actively support immunization acceptors in order to build and support vaccine acceptance resiliency. This paper presents evidence-informed strategies to achieve these goals.